Oral and esophageal cancer: Incidence, prevalence and correlation in general Indian Population: A retrospective study - Manish Khare; Yatindra Dewangan; Tarun Nayak; Dharmendra Kumar Singh; Vimal Vibhakar; Kumar Ramesh (Wolters Kluwer Medknow Publications, 2021)
Background: Squamous cell carcinoma is the most frequent head-and-neck malignancy and chiefly encompasses malignancies of the upper aerodigestive tract, including the oral cavity, nasal cavity, paranasal sinuses, nasopharynx, oropharynx, hypopharynx, pharynx, and larynx. Objectives: The current study was conducted to evaluate the incidence, prevalence, and correlation of oral and esophageal cancer in the Indian population. Materials and Methods: The present study was conducted on the basis of data collected from various government cancer hospitals in India. A total of 1000 patients of either sex admitted to the oncology ward with head-and-neck cancer from June 2018 to June 2020 were included in the study. Information regarding family history, deleterious habits, and immunity status was also collected from their medical records. The readings were recorded in a master chart, and data analysis was carried out statistically. Results: A total of 1000 patients (617 males and 383 females) between the age range of 38 and 86 years were selected for the study. A total of 425 out of 1000 patients had esophageal cancer, whereas, 575 patients had oral cancer. A total of 347 males and 228 females had oral cancer, whereas 270 males and 155 females had esophageal cancer. Among the patients with oral cancer, 44 presented with a history of cigarette smoking, 49 with bidi smoking, 140 with tobacco chewing, 142 with gutkha chewing, and 159 with betel quid chewing. Majority of the patients had a habit of consuming tobacco in smokeless form. Among the patients with esophageal cancer, 175 presented with a history of cigarette smoking, 136 with bidi smoking, 12 with tobacco chewing, 13 with gutkha chewing, and nine with betel quid chewing. Conclusion: The incidence of both types of cancer was high in older age group, particularly in those aged above 50 years. Males had a higher predilection rate than females for both cancer types. The incidence of oral cancer was higher than that of esophageal cancer. Majority of the patients with oral cancer had a history of tobacco consumption in smokeless form, whereas the ones with esophageal cancer reported with a history of tobacco consumption in smoked form.